ANTIPROLIFERATIVE EFFECT OF ALCOHOLIC EXTRACTS OF SOME GABONESE MEDICINAL PLANTS ON HUMAN COLONIC CANCER CELLS - Line-Edwige, M.; Tchouya, Feuya; Raymond, Guy; Francois, E.; Edouard, N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Extracts from Piptadeniastrum africanum Brenan (Mimosaceae), Petersianthus macrocarpus (Breauv) L. (Lecydaceae), Cissus debilis Planch (Vitaceae) and Dieffenbachia seguine Jacq. (Araceae) were tested in vitro for their antiproliferative activity on human colon cancer cell line (CaCo-2). The highest antiproliferative activities were obtained with the alcoholic extracts of the roots of Piptadeniastrum africanum (G-PAR), the leaves of Petersianthus macrocarpus (G-PMF) and the stem of Cissus debilis (G-CDL), with 50% inhibition concentrations (IC50) of 15 µg/ml, 17 µg/ml and 25 µg/ml respectively. Only one extract (leaves of Dieffenbachia seguine (G-DSF)) exhibited weak antiproliferative activity with 50% inhibition concentration (IC50) higher than 50 µg/ml.